Development of the DKMQ Element for Analysis of Composite Laminated Folded Plate Structures - Foek Tjong Wong; Kristofer Widjaja (Civil Engineering Dimension, 2018)
The discrete-Kirchhoff Mindlin quadrilateral (DKMQ) element has recently been developed for analysis of composite laminated plates. This paper presents further development of the DKMQ for analysis of composite laminated folded plates. In this development, a local coordinate system is set up for each element at its centroid. The DKMQ stiffness matrix is superimposed with that of the standard four-node plane stress quadrilateral element to obtain a 24-by-24 folded plate stiffness matrix in the local coordinate system. To avoid singularity of the stiffness matrix, a small stiffness coefficient is added in the entries corresponding to the drilling degrees of freedom. The local stiffness matrix and force vector are then transformed to the global ones and assembled. The accuracy and convergence of the folded plate element are assessed using a number of numerical examples. The results show that the element is accurate and converge well to the reference solutions.